2002
DOI: 10.1007/s005950200106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment for Synchronous Hepatic Metastases from Gastric Cancer with Special Reference to Long-Term Survivors

Abstract: These findings suggest that curative gastrectomy combined with HAI or systemic chemotherapy should be attempted for patients with primary tumors without serosal invasion or any other noncurative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…11,12,14 Before hepatectomy, we ruled out other sites of metastases in our patient, as previously suggested. 11,12,15 Multiple metastases, once recognized, are generally scattered throughout both lobes of the liver, as they were in our patient, who had additional metastases in segment four. However, we decided to perform hepatectomy based on other reports that the number of hepatic metastases is of little importance as a prognostic indicator, and that hepatectomy should not be abandoned simply because multiple tumors are present in the liver, considering the high survival rates achieved by complete resection.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…11,12,14 Before hepatectomy, we ruled out other sites of metastases in our patient, as previously suggested. 11,12,15 Multiple metastases, once recognized, are generally scattered throughout both lobes of the liver, as they were in our patient, who had additional metastases in segment four. However, we decided to perform hepatectomy based on other reports that the number of hepatic metastases is of little importance as a prognostic indicator, and that hepatectomy should not be abandoned simply because multiple tumors are present in the liver, considering the high survival rates achieved by complete resection.…”
Section: Discussionmentioning
confidence: 65%
“…11 Even if the metastases are potentially resectable, surgery for liver metastases from gastric cancer is controversial owing to the reported unpredictable and rarely longterm survival rates, the aggressive biologic behavior of gastric cancer, and quality of life issues. [11][12][13] Surgery may be considered for some patients with liver metastases from gastric cancer (whose selection criteria are not generally accepted) if complete resection seems feasible after careful pre-and intraoperative staging and may improve their prognosis. 11,12,14 Before hepatectomy, we ruled out other sites of metastases in our patient, as previously suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all patients with gastric cancer, 2-9% have synchronous liver metastases that are a frequent and crucial problem [2][3][4][5] because patients with metachronous metastases have a longer survival (5-year survival, 29%) than those with a synchronous disease (5-year survival, 6%) [6], and a synchronous resection of metastatic liver tumors does not contribute to a survival benefit [7]. In fact, a lot of studies have reported that the effect of hepatic resection for gastric liver metastases on survival was dubious [8][9][10][11], whereas some reports have demonstrated that only a hepatic resection for liver metastases with gastrectomy was able to obtain a long-term survival when both the primary tumor and metastatic lesions were potentially respectable [7,[12][13][14]. It is, thus, a key question whether or not a synchronous resection of liver metastases provides a survival benefit.…”
Section: Introductionmentioning
confidence: 99%
“…6 In contrast, Shirabe et al and Kunieda et al recommend aggressive chemotherapy rather than a surgical treatment as an effective treatment for the patient with gastric adenocarcinoma and liver metastases. 7,8 Yoshizumi et al report an exceptional case of a patient with gastric adenocarcinoma with metastases to both the liver and paraaortic lymph nodes and with direct invasion into the tail of the pancreas who survived for 12 years after surgery, as a result of extensive excision and aggressive chemotherapy. 9 The patient had the 5 following clinicopathologic features indicative of the potential for long-term survival in patients with gastric adenocarcinoma and liver metastases:…”
mentioning
confidence: 99%